1881 Ind. Rev. Stat. 366 - (:unkn) unknown (My University, 1881)
Crimes, § 1957: Prohibited maliciously or mischievously shooting a gun, rifle, pistol, or other missile or weapon, or throwing a stone, stick, club, or other substance at a vehicle. Punishable by imprisonment for 30 days to 1 year and a fine of $10-100.
Keywords: DISCHARGE